Utilization of cow dung for biogas to improve livestock breeders and MSME entrepreneurs' economy - Astrilia Damayanti; M Burhan Rubai Wijaya; Arie Taveriyanto; Ima Winaningsih; Luvena Salsabila; Anfita Aulia Sakinah; Kautsar Taqi Imanullah; Cyeva Primahasta (University of Merdeka Malang, 2024)
Sriwulan Village, located in Limbangan District, Kendal Regency, is home to both cattle farmers and several Micro, Small, and Medium Enterprises (MSMEs). The village has a farmer group named Ngudi Kawruh, managing around 20 cows. However, cow dung in the area has become a source of air pollution, and the four MSMEs still rely on Liquefied Petroleum Gas (LPG) for production. One effective solution to this issue is converting cow dung into biogas, which offers both environmental and economic benefits. This community service program aims to introduce appropriate technology for processing cow dung into biogas using biodigesters. The biogas is stored in portable containers, such as truck inner tires, while the biodigester output, in the form of slurry, is utilized as solid organic fertilizer. The program provides education on these concepts through posters, videos, demonstrations, and YouTube links to ensure broad community understanding. By implementing this technology, the program not only addresses environmental concerns and reduces dependence on LPG but also significantly enhances the economic potential of both the villagers and MSME entrepreneurs, promoting sustainable development.